2007
DOI: 10.1111/j.1532-5415.2007.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Everyday Function in Individuals with Psychometrically Defined Mild Cognitive Impairment in the Advanced Cognitive Training for Independent and Vital Elderly Study

Abstract: Results demonstrate the importance of MCI as a clinical entity that not only predicts progression to dementia, but also predicts functional declines in activities that are key to autonomy and quality of life. MCI classification guidelines should allow for functional changes in MCI, and clinicians should monitor for such changes. Preservation of function may serve as a meaningful outcome for intervention efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
81
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 34 publications
12
81
1
4
Order By: Relevance
“…8,[34][35][36] The present study contributes to understanding the natural history of functional change in MCI. Prior studies [9][10][11][12] have examined longitudinal changes in functional abilities in MCI using generic selfreport measures of functional ability such as the Lawton and Brody Instrumental Activities of Daily Living Scale. The convergent evidence from these studies indicates that persons with MCI experience increasing levels of difficulty in the performance of daily activities over time, that restriction in complex activities of daily living precedes limitations in more basic functional abilities, and that MCI patients who demonstrate functional difficulties at baseline have a higher risk of progressing to dementia over time.…”
Section: Effect Of Conversion To Dementia On MDC Trajectorymentioning
confidence: 99%
See 2 more Smart Citations
“…8,[34][35][36] The present study contributes to understanding the natural history of functional change in MCI. Prior studies [9][10][11][12] have examined longitudinal changes in functional abilities in MCI using generic selfreport measures of functional ability such as the Lawton and Brody Instrumental Activities of Daily Living Scale. The convergent evidence from these studies indicates that persons with MCI experience increasing levels of difficulty in the performance of daily activities over time, that restriction in complex activities of daily living precedes limitations in more basic functional abilities, and that MCI patients who demonstrate functional difficulties at baseline have a higher risk of progressing to dementia over time.…”
Section: Effect Of Conversion To Dementia On MDC Trajectorymentioning
confidence: 99%
“…The convergent evidence from these studies indicates that persons with MCI experience increasing levels of difficulty in the performance of daily activities over time, that restriction in complex activities of daily living precedes limitations in more basic functional abilities, and that MCI patients who demonstrate functional difficulties at baseline have a higher risk of progressing to dementia over time. [9][10][11][12] We built on these studies by using a performancebased instrument that decomposes a specific functional domain-MDC-into component abilities. We found that the consent ability of understanding declined over 3 years, whereas other consent abilities remained more stable.…”
Section: Effect Of Conversion To Dementia On MDC Trajectorymentioning
confidence: 99%
See 1 more Smart Citation
“…Precede a esta investigación la realizada por Wadley et al (2007) en la que se muestra la importancia del estudio del deterioro cognitivo en relación con las actividades de la vida diaria y la pérdida de funcionalidad en las mismas, siendo éstas, claves para la autonomía y la calidad de vida de la persona. Bowling (1994) define el estado funcional del anciano como el grado en que un individuo es capaz de desarrollar los papeles que tiene asignados libre de limitaciones físicas y/o mentales.…”
Section: Introductionunclassified
“…The greatest inherent challenge in diagnosing MCI is the inter-individual variability among older adults, both in intellectual function at a given age and in rates of decline over time. In different studies, objective neuropsychological measures have included multiple global and domain-specific tests (Jorm et al, 2005;Wadley et al, 2007;Allegri et al, 2008;Albert et al, 2011). Subjective cognitive concerns are sometimes assumed from the very fact of the patient's seeking services, or reflect spontaneous complaints by patients or families; at other times, they are elicited by a single question or a standardized questionnaire, and/or represent the clinician's impression (St. John et al, 2002;Arnaiz et al, 2004;Di Carlo et al, 2007).…”
Section: The Unbearable Lightness Of MCImentioning
confidence: 99%